philosophy with children, free teaching activity, stimulus, philosophical research with children, critical thinking - Luka M. Medenica; Milena S. Oparnica (University of Belgrade, Teacher Education Faculty, 2024)
Programs for automatic text correction and adaptation have an increasing influence on modern language didactics. Given that such tools are not used in teaching Serbian as a foreign language, the goal of our research was to determine the lexical minimums for level A1 in Serbian as a foreign language and create an algorithm for their detection, i.e., to take the first steps in developing a program for automatic text correction and adaptation. In the research, we used a methodology that relies on the linguo-didactics of Russian as a foreign language, taking into account the developed corpora of lexical minimums in that Slavic language and the existence of the online tool Textometr for checking the complexity of the text. In this way, we identified 783 lexemes that represent the list of lexical minimums for level A1 in Serbian as a foreign language. Then, for the purposes of the paper, we created an algorithm in the Python programming language, which we tested on a specific text and found certain shortcomings when it comes to lemmatization of the text. In the following period, it is necessary to refine the lemmatizer in order to develop a program for automatic text correction.